2017
DOI: 10.1021/jacs.7b11300
|View full text |Cite
|
Sign up to set email alerts
|

Privileged Role of Thiolate as the Axial Ligand in Hydrogen Atom Transfer Reactions by Oxoiron(IV) Complexes in Shaping the Potential Energy Surface and Inducing Significant H-Atom Tunneling

Abstract: An H/D kinetic isotope effect (KIE) of 80 is found at -20 °C for the oxidation of 9,10-dihydroanthracene by [Fe(O)(TMCS)], a complex supported by the tetramethylcyclam (TMC) macrocycle with a tethered thiolate. This KIE value approaches that previously predicted by DFT calculations. Other [Fe(O)(TMC)(anion)] complexes exhibit values of 20, suggesting that the thiolate ligand of [Fe(O)(TMCS)] plays a unique role in facilitating tunneling. Calculations show that tunneling is most enhanced (a) when the bond asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 92 publications
6
39
0
Order By: Relevance
“…The large KIE was attributed to tunnelling. 78 The different donors in these cases, however, clearly attenuate the FeO bond; Fe−O distances are 1.65 and 1.70 Å for the trans MeCN and thiolate complexes, respectively. 79,80 The latter distance is the longest recorded for an S = 1 iron(IV) oxo complex.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The large KIE was attributed to tunnelling. 78 The different donors in these cases, however, clearly attenuate the FeO bond; Fe−O distances are 1.65 and 1.70 Å for the trans MeCN and thiolate complexes, respectively. 79,80 The latter distance is the longest recorded for an S = 1 iron(IV) oxo complex.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Their experimental data [43] supported the predictions and gave rise to KIE exp ( 10 /DHA)=80 (T=‐20 °C), ∼60 (T=0 °C), indeed, much larger than KIE exp =10 for ( 1 /DHA ) [35c] . These values matched closely the theoretically computed values of Debasish, [8,41] and exclusively so for the S=2 process; KIE TC ( 10 )=58, 61 (T=25°, 0 °C) vs. KIE TC ( 1 )=13–14 (25 °C).…”
Section: But How Does One Probe Tsr and Msr By Experimental Means?mentioning
confidence: 99%
“…On September 3, 2017 Klein visited me in Aachen, wherein I participated in the satellite symposium of WATOC 17, and we discussed how to write the joint paper. By September 5 th , 2017 I went back to Berlin where I stayed for a whole month, and completed the ACR perspective, [8] while simultaneously working with Johannes and Larry on the collaborative manuscript [43] about the interplay of theory and experiment in the series of H‐abstraction reactions, which involve the TMC‐based oxidants and mostly DHA:…”
Section: But How Does One Probe Tsr and Msr By Experimental Means?mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in a previous study the axial thiolate ligand of [Fe IV (O)(TMCS)] + has been suggested to play a unique role in facilitating tunnelling, thereby resulting in a large KIE of 80 for DHA oxidation. 31 A contrasting effect is now demonstrated for the equatorial sulphur ligation, which reduces the tunnelling contribution to a minimum. The effect of N versus S donors in an otherwise identical ligand environment is also reflected in the higher oxygen atom transfer (OAT) ability of 1-trans relative to 2-trans (Table 1).…”
mentioning
confidence: 96%